Question

( p(x)=2 x^{4}-3 x^{3}-3 x^{2}+6 x-2 )
( x=frac{1}{2}, x=1 ) is solution
So ( (2 x-1)=0 ) and ( (x-1)=0 )
taking ( (x-1) ) outin common
( begin{aligned} p(x) &=(x-1)left(2 x^{3}-x^{2}-4 x+2right) p(x) &=(x-1)(2 x-1)left(x^{2}-2right) &=(x-1)(2 x-1)(x-2)(x+2) x=1 & frac{x-frac{1}{2}}{4} frac{x=2}{text { Othe raos }} end{aligned} )

# 08106 mind all the senos g if you knowo that hoo 205-323 - 302 = 600 -2, of its rexos are t an HINT : As I Is a zero of plx) then (224) is a polynomial

Solution